Study the effect of lifestyle modifications on fetomaternal outcomes in gestational diabetes mellitus - Agarwal, Aayushi; Dwivedi, Seema; Tyagi, Preeti; Dwivedi, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: GDM leads to varied outcomes on both mother and foetus. However, most of the adverse effects are preventable. Timely diagnosis, proper counselling, adequate follow up plays a vital role. Lifestyle modifications include dietary interventions, weight management, adequate physical activity and stress management and prevention of any ill habits affecting health of the patient. Methods: A study included pregnant women in their first trimester at their first antenatal visit. patients with DIPSI report >140 were taken into study. all of them were counselled regarding lifestyle interventions. Patients were followed and healthy lifestyle score was calculated. The patients who followed the advices were taken in group 1 and those that didn’t followed were taken in group 2. 100 participants of each group were followed. Follow ups were done to see the outcomes till postpartum period. Results: The study found that Group 1 had better glycaemic control, more vaginal deliveries, and a shorter labor duration. The average baby weight was 97% in Group 1, slightly lower than in Group 2. NICU admissions were also lower in Group 1, and significant differences were observed in antepartum, intrapartum, and postpartum complications. Conclusions: The study shows that lifestyle modifications are an important part of management of GDM. Adherence to these changes leads to better glycaemic control and thus better maternal and foetal outcomes.